2017
DOI: 10.4236/ss.2017.82009
|View full text |Cite
|
Sign up to set email alerts
|

Review of Thoracic Endovascular Aneurysm Repair (TEVAR), Spinal Cord Ischemia (SCI), Cerebrospinal Fluid (CSF) Drainage and Blood Pressure (BP) Augmentation

Abstract: The object of this review is to examine the role of TEVAR in causing SCI. The anatomy and physiology of blood flow to the spinal cord is examined. The role of auto regulation of blood flow within the spinal cord is also examined. This review examines the reported results from the scientific literature of the effect of thoracic aortic aneurysm repair on spinal cord blood flow. In the light of these findings several conclusions can reasonably be reached. These conclusions are that the development of SCI can reas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…One debated method of maintaining SCPP is through cerebrospinal fluid drainage (CSFD), for which the body of literature remains divided. Various studies have reported reduced risks of SCI following CSFD, and patients who receive routine prophylactic CSFD may receive the greatest benefit (10)(11)(12)(13). Other studies suggest that SCI rates remain similar between drained and non-drained patients (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…One debated method of maintaining SCPP is through cerebrospinal fluid drainage (CSFD), for which the body of literature remains divided. Various studies have reported reduced risks of SCI following CSFD, and patients who receive routine prophylactic CSFD may receive the greatest benefit (10)(11)(12)(13). Other studies suggest that SCI rates remain similar between drained and non-drained patients (14,15).…”
Section: Introductionmentioning
confidence: 99%